The Impact of CBM-Based Counseling Learning with Relaxation Techniques in Reducing Anxiety - Miftahul Jannah; Yeni Karneli; Rezki Hariko; Zadrian Ardi (International Journal of Education and Teaching Zone, 2025)
Counseling education plays a crucial role in both classroom and extracurricular learning contexts. It can serve as a foundational paradigm for educational practices in society. Substance Use Disorder (SUD) presents significant global and local challenges that can disrupt the educational landscape in Indonesia, particularly due to its high prevalence in correctional institutions, which often leads to accompanying psychological issues such as anxiety that hinder rehabilitation. This study examined the effectiveness of group counseling using a Cognitive Behavior Modification (CBM) approach combined with relaxation techniques in reducing anxiety among incarcerated individuals with SUD at Padang Class IIA Correctional Institution. Employing a quantitative quasi-experimental design with a pretest–posttest control group, 16 participants were selected through purposive sampling and divided into experimental (n=8) and control (n=8) groups. Anxiety was measured using a 32-item Likert scale adapted from Nevid et al. (2018), and data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. The findings revealed a significant decrease in anxiety levels in the experimental group (mean pretest = 136.38, posttest = 54.38, p = 0.012, N-Gain = 78.56%), outperforming the control group (p = 0.027). These results support the role of CBM in restructuring maladaptive thinking and highlight the contribution of relaxation techniques to emotional stability. This intervention provides a promising evidence-based option for mental health programs in Indonesia and offers valuable insights for policy development to enhance rehabilitation and promoting high quality education, especially in the world of educational psychology learning.